O bônus de contratação e a cláusula de permanência - Malta, Guilherme Tadeu Cruz (2019)
One of the ways US and European large companies have to recruit senior employees is through the payment of a sum called a hiring bonus, also known as hiring bonus, sign in bonus or retainer fee. The purpose of the value is to attract the employee to the new company, thereby incurring the loss resulting from the resignation from the previous employment. On the other hand, the acceptance is accompanied by a stay clause, in which the executive agrees to remain in the company during a period agreed by the parties, under penalty of return of the sum if this part resignation before. The paper dealt with the concept of the hiring bonus and the two major controversies that surround the theme: its legal nature and the validity of the stay clause. First, a differentiation was made between the bonus and the loan agreement. It was also the differentiation between the hiring bonus, the gloves paid to the professional soccer player and the pass. After that, an analysis of the amounts paid during the duration of the employment contract was made. The stay clause was dealt with according to the three most common forms of termination of the employment contract: dismissal, dismissal without just cause and dismissal motivated. Finally, the position of CARF and TST on the topic was analyzed